1995
DOI: 10.1002/ajmg.1320570223
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm studies in neuronal ceroid‐lipofuscinosis (NCL)

Abstract: Sleep disorders are common in NCL patients. The patients have problems such as frequent awakenings, difficulties with sleep onset, nightmares, and night terrors. The aim of the study was to examine whether the sleep disturbance in NCL can be explained on the basis of desynchronised circadian rhythms. Therefore we studied diurnal patterns of melatonin, cortisol, body temperature, and motor activity of 14 patients. The group consisted of 8 JNCL patients, 5 INCL children, and one boy with Jansky-Bielschowsky dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…22,23 Furthermore, studies have linked chronic epilepsy to permanent circadian phase shifts, 24,25 with the presence and degree of abnormality likely dependent on the severity of disease. 26 Aggregating data from subjects with large circadian phase differences relative to each other would likely smear the distributions to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, studies have linked chronic epilepsy to permanent circadian phase shifts, 24,25 with the presence and degree of abnormality likely dependent on the severity of disease. 26 Aggregating data from subjects with large circadian phase differences relative to each other would likely smear the distributions to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis are studies of circadian temperature recordings in NCL patients showing significant disturbances in body temperature rhythms. Researchers showed that patients with INCL have maximal temperature in the morning, whereas controls had higher temperatures in the afternoon (20). It is also noteworthy that the only INCL patient in our series who did not develop hypothermia was the youngest patient (Patient 8) who had not yet developed neurological deficits at the time of first anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Most symptomatic treatment studies in NCL have come from what we know from other diseases – but very few studies have been done specifically in NCL patients. In INCL these have been: Lamotrigine for epilepsy [ 19 21 ]; Transdermal fentanyl for pain [ 22 ]; Melatonin for sleep/circadian rhythm disturbance [ 23 25 ]; and hematopoietic stem cell transplant – umbilical cord blood and bone marrow transplant for disease modification [ 26 ]. These treatments, with a limited number of participants, are difficult to interpret because the studies are occurring at a time of rapid development, which significantly increases the variability between subjects, making outcomes difficult to measure.…”
Section: Pipeline For Drug Developmentmentioning
confidence: 99%